The English of Bosnia and Herzegovina. Issue 4 (12th November 2018) - Dubravac, Vildana; Brdarević‐Čeljo, Amna; Bećirović, Senad
Abstract: With the number of world Englishes steadily increasing, the impact of 'core' English varieties is weakening. However, the influence of two varieties, namely standardised American English and standardised British English, seems to be dispersed across all areas, in particular across peripheral varieties. Due to the difference in their demographic weight and the institutional support they receive, these two varieties do not secure a balanced representation in the peripheral layer. The current study investigates whether 132 university‐level Bosnian learners of English report using particular items of American or British English at the levels of pronunciation, spelling, grammar and vocabulary.